Ethical leadership and unethical pro-organizational behavior: A moderated mediation model of affective commitment and authenticity at work - Venâncio, Sara Filipa Gonçalves (2016)
Recently, unethical conduct in the workplace has been a focus of literature and media. Unethical pro-organizational behavior (UPB) refers to unethical conduct that employees engage in to benefit the organization. Given the complexity of UPB, there is an increasing need to understand how and under what conditions this attitude originates within organizations. Based on a sample of 167 employees and seven organizations, results support the moderated mediation model. An ethical leader increases employees’ organizational affective commitment which increases the likelihood to engage in UPB. However, the indirect relationship diminishes when employees feel authentic at work.